Involvement of Dual Strands of miR-143 (miR-143-5p and miR-143-3p) and Their Target Oncogenes in the Molecular Pathogenesis of Lung Adenocarcinoma - Sanada, Hiroki (Int J Mol Sci, 2019)
Our analyses of tumor-suppressive microRNAs (miRNAs) and their target oncogenes have identified novel molecular networks in lung adenocarcinoma (LUAD). Moreover, our recent studies revealed that some passenger strands of miRNAs contribute to cancer cell malignant transformation. Downregulation of both strands of the miR-143 duplex was observed in LUAD clinical specimens. Ectopic expression of these miRNAs suppressed malignant phenotypes in cancer cells, suggesting that these miRNAs have tumor-suppressive activities in LUAD cells. Here, we evaluated miR-143-5p molecular networks in LUAD using genome-wide gene expression and miRNA database analyses. Twenty-two genes were identified as potential miR-143-5p-controlled genes in LUAD cells. Interestingly, the expression of 11 genes (MCM4, RAD51, FAM111B, CLGN, KRT80, GPC1, MTL5, NETO2, FANCA, MTFR1, and TTLL12) was a prognostic factor for the patients with LUAD. Furthermore, knockdown assays using siRNAs showed that downregulation of MCM4 suppressed cell growth, migration, and invasion in LUAD cells. Aberrant expression of MCM4 was confirmed in the clinical specimens of LUAD. Thus, we showed that miR-143-5p and its target genes were involved in the molecular pathogenesis of LUAD. Identification of tumor-suppressive miRNAs and their target oncogenes may be an effective strategy for elucidation of the molecular oncogenic networks of this disease.